Early diabetic eye damage: Comparing detection methods using diagnostic power - Rai Bhim B; van Kleef Joshua P; Sabeti Faran; Vlieger Robin; Suominen Hanna; Maddess Ted (Elsevier Inc, 2025)
It is now clear that retinal neuropathy precedes classical microvascular retinopathy in diabetes. Therefore, tests that underpin useful new endpoints must provide high diagnostic power well before the onset of moderate diabetic retinopathy. Hence, we compare detection methods of early diabetic eye damage. We reviewed data from a range of functional and structural studies of early diabetic eye disease and computed standardized effect size as a measure of diagnostic power, allowing the studies to be compared quantitatively. We then derived minimum performance criteria for tests to provide useful clinical endpoints. This included the criteria that tests should be rapid and easy so that children with type 1 diabetes can be followed into adulthood with the same tests. We also defined attributes that lend test data to further improve performance using Machine/Deep Learning. Data from a new form of objective perimetry suggested that the criteria are achievable.